2008
DOI: 10.1055/s-2007-965059
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors in Resected T3 Non-Small Cell Lung Carcinoma: Perineural Invasion as a New Prognostic Factor

Abstract: Incomplete resection, N2 disease, vascular and perineural invasion were found to be prognostic indicators for the survival of T3 NSCLC patients. Of these indicators, perineural invasion was found to be the strongest predictor of poor prognosis and independently affected the patients' survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
5
1
Order By: Relevance
“…In the present study, the rate of occurrence of major complications was 7.0 % (empyema, chylothorax, and postoperative bleeding), and the postoperative mortality rate was 2.3 %. According to most of previous studies, N1 or N2 disease was a significant unfavorable prognostic factor in comparison with T3N0M0 disease [8,9,[18][19][20][21][22][23]. However, in the present study, no difference in the prognosis was observed between patients with and without lymph node metastasis, likely because there were a too few patients with lymph node metastasis.…”
Section: Discussioncontrasting
confidence: 62%
“…In the present study, the rate of occurrence of major complications was 7.0 % (empyema, chylothorax, and postoperative bleeding), and the postoperative mortality rate was 2.3 %. According to most of previous studies, N1 or N2 disease was a significant unfavorable prognostic factor in comparison with T3N0M0 disease [8,9,[18][19][20][21][22][23]. However, in the present study, no difference in the prognosis was observed between patients with and without lymph node metastasis, likely because there were a too few patients with lymph node metastasis.…”
Section: Discussioncontrasting
confidence: 62%
“…The presence of cancer cells in the perineurium is mostly associated with poor prognosis and high recurrence in pancreatic, colorectal, and gastric cancers, but not in invasive breast carcinoma (12). Highly contradictory results have been reported on the "inherent positive neuronal tropism" of lung cancer and the prognostic value of the perineural invasion in the lungs (13,14). The involvement of the PNS in the formation of distant lung cancer metastases has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…The predictive effect of lymphovascular invasion on local–regional failure [ 19 ] and distant recurrence [ 26 , 27 ] has been demonstrated before. Visceral pleural invasion [ 19 , 22 ] and perineural invasion [ 20 , 21 ] are also considered prognostic factors of poor PFS. Our results suggest that pathological features are critical and recognizing patients with higher risk of recurrence might facilitate the selection of adjuvant systemic treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue slides stained with the hematoxylin–eosin stain, immunohistochemistry stain, or elastic stain were reviewed by experienced pathologists. The presence of tumor cells in the lymphatic or vascular lumen, the space around nerves, or the visceral pleura was defined as lymphovascular invasion [ 19 ], perineural invasion [ 20 , 21 ], or visceral pleural invasion [ 22 ], respectively. Margin involvement was defined as microscopic residual disease at the resection margin.…”
Section: Methodsmentioning
confidence: 99%